CYP2D6 Genotype and Pharmacovigilance Impact on Autism Spectrum Disorder: A Naturalistic Study with Extreme Phenotype Analysis - Pura Ballester; Cristina Espadas; Susana Almenara; Jordi Barrachina; Javier Muriel; Enrique Ramos; Natalia Toral; César Belda; Ana M. Peiró (MDPI AG, 2023)
The long-term use of psychopharmacology medications in autism spectrum disorder (ASD) hitherto remains controversial due to a lack of evidence about safety and tolerability. In this regard, genotyping the metabolizing enzyme cytochrome P450 (CYP) 2D6, especially its extreme phenotypes, could help to prevent drug-related adverse reactions or adverse events (AEs). There are several medications warranting CYP2D6 screening that are consumed by people with ASD, such as risperidone and aripiprazole to name a few. A naturalistic observational study was carried out in participants with ASD to analyze the influence of the CYP2D6 phenotype in drug tolerability using a local pharmacovigilance system created for this study. In this case, AEs were identified from participants' electronic health records (EHRs) and paper registries. Other variables were collected: socio-demographic information, comorbidities, and psychopharmacology prescriptions (polypharmacy defined as ≥4 simultaneous prescriptions) and doses. The genetic analysis included allelic discrimination (CYP2D6*1, *2, *3, *4, *5, *6, *10, *17, and *41) and copy number variations. All of these were used to determine theoretical phenotypes of the metabolic profiles: poor (PM); intermediate (IM); normal (NM); and ultra-rapid (UM). Sex differences were analyzed. A total of 71 participants (30 ± 10 years old, 82% male, 45% CYP2D6 NM phenotype (32 participants)) with a median of 3 (IQR 2-4) comorbidities per person, mainly urinary incontinence (32%) and constipation (22%), were included. CYP2D6 UM showed the highest rate of polypharmacy, whilst, IM participants had the highest rates of neurological and psychiatric AEs, even worse if a CYP2D6 inhibitor drug was prescribed simultaneously. CYP2D6 pharmacogenomics and the monitoring of new antipsychotic prescriptions may make a difference in medication safety in adults with ASD. Particularly in those with psychopharmacology polymedication, it can help with AE avoidance and understanding.